PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA DEDICADA A LA ELABORACIÒN Y COMERCIALIZACIÓN DE CREMAS FACIALES MEDICINALES A BASE DE COL, EN LA CIUDAD DE LOJA - CORDOVA CAMPOVERDE, THALIA LILIANA (2016)
Trends in today's world and globalization standards of beauty cosmetic boost consumption but consumer demands become increasingly complex. There is now a concern of consumers use cosmetics based on natural products, as in the case of face creams that nourish the skin besides fulfill other functions such as regenerating seek satisfactory cosmetic results, without sacrificing the natural state skin with harmful chemicals. With the above background, it aims to contribute to the socio-economic development and to encourage a significant economic investment; to perform a "PROJECT FEASIBILITY FOR THE IMPLEMENTATION OF A COMPANY DEDICATED TO THE PROCESSING AND MARKETING OF MEDICAL Face creams COL BASED IN CITY OF LOJA" that provides the ability to have a product with natural benefits while will make known the benefits of cabbage on the skin, a previous study of trends and demands made for these reasons the present investigation was based on information collected and investigated which a clear synthesis was obtained following an information analysis to conclude the research detailing the importance and improvement of investigation, drawing upon sources of information and consultation for the development of work where materials and methods that contributed profits of the study object was used, leading to results data which was structured and designed the preparation of the proposal according to the market study where they proceeded to the collection of information through the application of surveys to buyers and sellers, which are tabulated, processed and interpreted getting the results determined the demand, supply, price, presentation, 6 marketing channels and marketing strategies for bringing the technical study determined the optimal location of the new production, analysis of product engineering, physical distribution is developed plant, installed capacity, determination of equipment and materials and supplies required for production inputs within the technical study has the organizational study defines the company from the legal point of view in this case as Limited Liability Company, was also included company organization by presenting organizational structural, functional positioning and operating manuals. The investment for the project is $ 64,684.68; funding follows internal capital consists of $ 36,684.68 and $ 28.000,00 external determined; since this amount is budgeted to cover costs of production that determined the retail price, to make the point of balance, with certain income and expense for the company, with which the evaluation of the project was developed by the application of the assessment criteria where the favorable net present value of $ 182.645,61 with an internal rate of return of 65.48%, that for every dollar invested earnings of 44 cents will get detailed., therefore investment will recover in 1 year, 7 months and 24 days, taking into account increased costs and decreased 21.20% from 14.50% in revenues, these results showed the viability and profitability of the project, so what conclusions and recommendations are determined based on what developed in the research; Finally the bibliography and appendices detailing the references taken as the basis of specified information and support.